One pot ligand exchange method for a highly stable Au-SBA-15 catalyst and its room temperature CO oxidation - Soni, Yogita; Kavya, I.; Ajithkumar, T. G.; Vinod, C. P. (Chemical Communications, 2018)
A modified deposition precipitation (DP) method has been developed to address a fundamental issue of supporting well dispersed Au nanoparticles on silica. Ammonium chloride (NH4Cl) plays an important role in in situ modifying the gold precursor (HAuCl(4)3H(2)O) solution allowing facile deposition of gold NPs in the channels of SBA-15. The Au-SBA-15 catalyst (2.8 wt%) synthesized by this procedure showed 100% conversion for CO oxidation at room temperature with excellent stability at room temperature and high temperature.